The effect of upper- and lower-body exercise on next-day postprandial triglycerides in healthy young men - Zhong, Zhentao; Miyachi, Motohiko; Tanisawa, Kumpei (Frontiers in Physiology, 2024)
Aims High non-fasting triglycerides (TG) concentration is linked to the development of atherosclerosis, and physical activity is commonly recommended to reduce postprandial TG concentration and cardiovascular diseases. Previous studies have demonstrated that acute whole-body (walking and running) or lower-body (leg cycling) aerobic exercise reduces postprandial TG. However, it is unclear whether upper-body exercise (i.e. arm-cranking) with sufficient energy expenditure lowers postprandial TG. Therefore, this study aimed to evaluate the effects of energy-matched upper- and lower-body exercises on postprandial TG concentrations the next day in healthy young men. Method and Materials Fifteen healthy young men (age 22.5 ± 1.7 years, height 173.8 ± 5.7 cm, body mass 68.2 ± 8.5 kg, peak oxygen uptake 48.0 ± 5.5 mL/min/kg and physically active) participated in a three-arm crossover trials: 1) arm-cranking, 2) leg-cycling exercise at 70% of mode-specific peak oxygen uptake to induce a net energy expenditure of 1,255 kJ, or 3) rested between 16:00 and 17:00 h on day 1 and consumed two standardised meals for breakfast (10:00 h) and lunch (13:00 h) on day 2. The mean macronutrient content of the breakfast was 44.9 ± 5.6 g fat, 104.8 ± 13.0 g carbohydrate, and 29.4 ± 3.6 g protein, which provided 3.95 ± 0.49 MJ energy (43% fat, 45% carbohydrate, and 12% protein), and that of the lunch was 45.2 ± 5.6 g fat, 106.7 ± 13.2 g carbohydrate, and 33.9 ± 4.2 g protein, which provided 4.06 ± 0.50 MJ energy (42% fat, 44% carbohydrate, and 14% protein). Results Time-averaged postprandial serum TG concentrations over 8 h differed among trials (main effect of trial p < 0.001) and were lower in the upper- and lower-body exercise trials than in the control trial (1.46 ± 0.54 vs. 1.50 ± 0.69 vs. 1.79 ± 0.83 mmol/L, respectively). The incremental TG area under the curve (AUC) (main effect of trial, p = 0.012) was 39% and 37% higher in the control trial than in the upper- and lower-body exercise trials (p = 0.025 and p = 0.033, respectively). There were no significant differences in incremental TG AUC between the upper- and lower-body exercise trials. Conclusion An acute bout of energy-matched upper- and lower-body exercises similarly lowered postprandial TG concentrations the following day in healthy young men. Trial registration number: UMIN000045449. Date of registration: 10 September 2021.